im not sure how to do it
The way you did it is fine. As the lesson you studied (in the link, provided earlier) explained and demonstrated, you use the log rules to break the given log into separate terms which will
relate to the given values. So the missing steps (that you'll probably want to include in your hand-in homework) make the solution look like:. . . . .
log(36) = log(9*4) = log(9) + log(4). . . . .
) + log(4) = 2*log(3) + log(4). . . . .
= (2)(0.62) + 0.45
...and so forth.
The other one works the exact same way.